Peran Media Massa Lokal dalam Penanganan Stunting di Sulawesi Tenggara - Mahdar (CV. ITTC INDONESIA, 2023)
Efforts to reduce stunting rates in Indonesia, including in Southeast Sulawesi, require cooperation with various parties, one of which is the mass media. In Kendari, the local mass media is involved to take part in handling stunting. This involvement was manifested in the form of a cooperation agreement between the National Population and Family Planning Agency (BKKBN) Representative of Southeast Sulawesi Province and 11 local media. All of these media have an obligation to publish information about stunting. This study aims to determine the role of the local mass media in handling stunting in Southeast Sulawesi. Through the functions of the media, namely the functions of information, education, entertainment and social control, the local mass media in Kendari also plays a role in helping the government to reduce the stunting rate in Southeast Sulawesi which is still high, namely 27.7 percent.